Supporting and Empowering Municipal Functions and Staff - Keicho, Toshiaki; International Recovery Platform (World Bank, Washington, DC, 2013)
A mega disaster can destroy government offices and kill public officials. In the Great East Japan Earthquake (GEJE), many municipalities in Tohoku suffered serious damage to their office buildings and incurred considerable staff losses, which hampered their disaster response timing and effectiveness. To compensate for this, many kinds of partnership arrangement were formed between localities in the affected areas and their counterparts in unaffected areas. Formalizing these partnership arrangements and building local government capacities to deal with emergency situations are key success factors for developed and developing countries alike. One of the most interesting developments after March 11 was that a variety of partnership arrangements evolved between local governments affected by the disaster and those that were unaffected. The roles that local governments must play in the aftermath of a disaster can be critical. But clear roles and responsibilities must first be assigned to each tier of government, specifying what needs to be done by which level in case of a disaster, and to strengthen their capacities accordingly.